Other Branches of Science Are Necessary to Form a Lawyer: Teaching Public Health Law in Law School - Goodman, Richard A.; Lazzarini, Zita; Moulton, Anthony D.; Burris, Scott; Elster, Nanette R.; Locke, Paul A.; Gostin, Lawrence O. (The Journal of law, medicine & ethics, 2002)
Over two hundred years ago, Thomas Jefferson suggested the need for a broader legal curriculum. As the twenty-first century begins, the practice of law will increasingly demand interdisciplinary knowledge and collaboration — between those trained in law and a broad range of scientific and technical fields, including engineering, biology, genetics, ethics, and the social sciences. The practice of public health law provides a model for both the substantive integration of law with science, and for the way its practitioners work. In addition, public health law also provides a model for interdisciphuy and integrative teaching.